HIV Status among Tuberculosis Patients Registered in a Tertiary Care Hospital of Army, Kathmandu, Nepal - Lee Budhathoki; Rajesh Khatri; Rajendra Neupane; Leela Paudel; Lochana Shrestha; Parag Karki (Nepal Journal of Public Health, 2026)
Background: Tuberculosis (TB) is a huge public health issue in Nepal. TB can coexist with Human immunodeficiency virus (HIV) infection. TB-HIV co-infection identification and prompt treatment is necessary in army personnels because of the propensity to spread early as many live together in dormitories and share similar lifestyles. Methods: A cross-sectional observational study was conducted in DOTS center of Shree Birendra Hospital (SBH) in 46 patients from January-April, 2023 using non-random purposive sampling. Data was collected with proforma containing preformed questionnaires through face to face interview and observation of treatment reports. Data was entered and analysed in Microsoft Excel. Ethics clearance was taken from the Institutional Review Committee (Registration No 471, December 2022). Results: The prevalence of HIV among TB patients was 2.2%. The mean age was 44.0 ±17.98 years and majorities of the participants were married males. Extrapulmonary TB constituted 29(63.1%). Majority of participant consumed alcohol (35) and smoked tobacco products (29) and 18 patients had close contact with TB cases. 3(6.5%) cases were relapse case. Conclusion: This study showed higher prevalence of HIV among tuberculosis patients in military than the normal population. Efforts to identify HIV among TB patients and vice versa is key to reducing this lethal combination so screening for HIV in all TB patients of Nepali Army is advised at a policy level.